2014
DOI: 10.1111/apa.12535
|View full text |Cite
|
Sign up to set email alerts
|

Chickenpox and stroke in children: case studies and literature review

Abstract: Chickenpox should be considered in differential diagnosis of ischaemic stroke in healthy children who fit the clinical and radiological typical profile of PVCA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 15 publications
0
15
1
Order By: Relevance
“…Several studies and case series suggest that varicella triggers strokes in children[1, 5]. However, we found no evidence in this ecologic analysis that rates of pediatric strokes have changed among children 0–17 years of age during our study interval to parallel the large declines in rates of varicella that we observed.…”
Section: Discussioncontrasting
confidence: 76%
See 2 more Smart Citations
“…Several studies and case series suggest that varicella triggers strokes in children[1, 5]. However, we found no evidence in this ecologic analysis that rates of pediatric strokes have changed among children 0–17 years of age during our study interval to parallel the large declines in rates of varicella that we observed.…”
Section: Discussioncontrasting
confidence: 76%
“…While generally self-limited, it was responsible for significant morbidity and mortality due to serious secondary bacterial infections, pneumonia, cerebellar ataxia, transverse myelitis, encephalitis, Reye Syndrome, myocarditis, hepatitis, and hemorrhagic complications[1]. Strokes have also been putatively linked to acute varicella[15]. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other pathogenetic hypotheses include the following: Hematologic spread of VZV; a postinfection vascular immune-mediated reaction; sympathetic activation due to local irritation caused by infection in the superior cervical ganglion; VZV-linked thrombotic vascular occlusion for direct endothelial damage; an acquired transient deficiency of proteins S/C. [ 4 ]…”
Section: Discussionmentioning
confidence: 99%
“…[ 2 3 ] Another complication is postvaricella stroke with an incidence of 1/15,000. [ 4 ] The basal ganglia are the most involved part of the brain in VZV vasculopathy,[ 5 ] where the angiopathy causes transient ischemic attack (TIA) and/or stroke with transient or permanent hemiplegia. The differential diagnosis for VZV vasculopathy includes other diseases that cause hemiplegia, such as trauma, congenital heart disease, vascular malformations, hypercoagulable states, malignancy, congenital errors of metabolism, and infections.…”
Section: Introductionmentioning
confidence: 99%